PENYESUAIAN DIRI DAN DUKUNGAN KELUARGA DENGAN KEPRIBADIAN TANGGUH SANTRIWATI TAHUN PERTAMA PONDOK PESANTREN X CIKARANG: PENYESUAIAN DIRI DAN DUKUNGAN KELUARGA DENGAN KEPRIBADIAN TANGGUH SANTRIWATI TAHUN PERTAMA PONDOK PESANTREN X CIKARANG - Oktaviani, Ellsa Azma; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACTThis study aims to determine the relationship between personal adjustment and family support with hardiness infirst year students of X Islamic Boarding School in Cikarang. Research uses quantitative methods. The samplingtechnique of this study uses proportional random sampling with a sample of 135 students. Data retrieval uses aLikert scale consisting of, hardiness scale, personal adjustment scale and family support scale using SPSS 22.00for windows. The result of bivariate correlation technique analysis shows that there is a significant relationshipwith the positive direction between personal adjustment and hardiness, the correlation coefficient value (rxy1 ) is0.712 with p = 0.000 (p <0.05), and there is a significant relationship with the positive direction between supportfamily with hardiness obtained correlation coefficient value (rxy2 ) of 0.433 with p = 0.000 (p <0.05). To testthe hypothesis with multivariate correlation technique, R value is 0.725 which means that there is a significantrelationship with the positive direction between personal adjustment and family support with hardiness. Theeffective contribution between personal adjustment and family support is 52.5% while the remaining 47.5% is acontribution other factors not examined.